Hedge Accounting in the Consolidated Financial Statements of WIG 40 Companies - Hyży, Maciej (Rachunkowość zabezpieczeń w skonsolidowanych sprawozdaniach finansowych spółek z WIG-40, 2024)
Aim: To check whether WIG 40 companies apply hedge accounting, and if so, do the effects of applying hedge accounting significantly affect the financial performance of these companies? Does hedge accounting improve the efficiency of operations by WIG-40 companies? Methodology: The article uses the following research methods: literature review, analysis of legal acts related to hedge accounting, verification of consolidated financial statements. Results: The results show that a significant portion of WIG-40 companies do not apply hedge accounting. Implications and recommendations: It is recommended to conduct further research related to hedge accounting for a larger number of companies listed on the Stock Exchange, and try to answer the question of what is the reason for the lack of application of hedge accounting on a larger scale. Originality/value: The article verified the use of hedge accounting and its impact on the financial statements of the WIG-40 companies studied.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 4, s. 1-9
Keywords: hedge accounting; derivative financial instruments; hedge effectiveness; financial performance; rachunkowość zabezpieczeń; pochodne instrumenty finansowe; efektywność zabezpieczeń; wyniki finansowe